Applications of muscle oxygen saturation analysis in cycling performance assessment: a systematic review - Cesanelli, L.; Ylaite, B.; Leite, N.; Calleja-González, J. (Journal of Science and Cycling, 2021)
Purpose: Cycling performance is the result of the interplay among a wide range of variables. Different methodological approaches have been described during last 50 years in order to evaluate and understand cycling performance. Our main aim was to systematically review the applications of muscle oximetry in cycling performance assessment.